Computers Introduction For Elementary School Students Using Game-Based Learning - Perbawa, Doddy Satrya; Rapiyanta, Paulus Tofan (International Journal of Business, Law, and Education, 2024)
Learning media facilitates teacher's role in conveying knowledge to students. One of learning tools that teachers can use in their learning is interactive media. Introduction to computers is important in today's digital era because it can build knowledge and understanding about computers and improve learning skills. This is possible because computer's ability to combine text, sound, color, images, movement and video and create an interactive process. This research aims to help students in grade 1 or 2 of elementary school to more easily understand and master basic computer use. In this application there are computer learning menu, typing and cursor learning. Computer learning menu consists of definitions, learning videos and quizzes. Learning to type and cursor consists of understanding, practice and mini games. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) model is used in developing system used in this research.